2014
DOI: 10.1097/md.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E immunopositive Melanomas Show Low Frequency of Heterogeneity and Association With Epithelioid Tumor Cells

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Therefore, most cutaneous melanomas have a homogeneous BRAF mutation status within a single tumor. Indeed, several studies have found relatively homogeneous BRAF V600E expression in melanoma [27][28][29][30]. However, some studies, including our previous one, have shown definite intratumor heterogeneity of BRAF V600E [16,31,32].…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, most cutaneous melanomas have a homogeneous BRAF mutation status within a single tumor. Indeed, several studies have found relatively homogeneous BRAF V600E expression in melanoma [27][28][29][30]. However, some studies, including our previous one, have shown definite intratumor heterogeneity of BRAF V600E [16,31,32].…”
Section: Discussionmentioning
confidence: 66%
“…While the finding of 100% concordance may not be replicated in future larger series or in other populations, taken in the context of previous studies our findings add further support to the conclusion that differences in BRAF status between primary and metastatic sites as determined by IHC are significantly less common than discordance as assessed by PCR. [18][19][20][21][22][23][24]37 Our description of a case of apparent PCR discordance which was subsequently shown to be due to a false negative at one site suggests that some of this difference in findings between methods may be due to technical difficulties with obtaining accurate molecular data from small tumor deposits.…”
Section: Discussionmentioning
confidence: 89%
“…It is noteworthy that in previous work on BRAF status discordance between primary and metastatic melanoma, the pooled rate of discordance was lower in studies using IHC to detect mutant protein, compared with those using DNA‐based approaches . Across seven studies using the VE1 anti‐V600E BRAF antibody, the mean discordance was 5.6% . By contrast, the mean discordance was 14% in DNA‐based studies .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Tumor heterogeneity refers to the existence of subpopulations of cells with distinct molecular variation within individual tumors (intra-tumor heterogeneity) or between tumors at different sites within a patient (inter-tumor heterogeneity). Previous studies have revealed that melanoma is associated with inter-tumor heterogenous BRAF status in about 4%-25% of patients [17,18]. If wild-type BRAF melanoma cells are exposed to BRAF inhibitors, the melanoma cells may paradoxically activate the MAPK pathway [18], causing adverse effects.…”
Section: Introductionmentioning
confidence: 99%